2019
DOI: 10.1371/journal.pone.0217552
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes downregulates renal adenosine A2A receptors in an experimental model of hypertension

Abstract: Studies on diabetic nephropathy rarely take into account that the co-existence of diabetes and hypertension is frequent and further aggravates the prognosis of renal dysfunction. Adenosine can activate four subtypes of adenosine receptors (A 1 , A 2A , A 2B and A 3 ) and has been implicated in diabetic nephropathy. However, it is not known if, in hypertensive conditions, diabetes alters the presence/distribution profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…In the present study, we observed that SHR-STZ rats treated with CADO (but not with DPSPX) for seven days showed higher expression of adenosine A 2A receptors in SG, PCT, and DCT than control SHR-STZ rats. Interestingly, this difference was observed in the same renal structures where we previously demonstrated a decrease in the expression of the adenosine A 2A receptor associated with the induction of diabetes in SHR when compared with normoglycemic SHR [ 29 ]. Furthermore, we previously reported that CADO treatment improved glucose metabolism (decreased hyperglycemia and glycosuria) and renal function (decreased proteinuria) [ 20 ].…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…In the present study, we observed that SHR-STZ rats treated with CADO (but not with DPSPX) for seven days showed higher expression of adenosine A 2A receptors in SG, PCT, and DCT than control SHR-STZ rats. Interestingly, this difference was observed in the same renal structures where we previously demonstrated a decrease in the expression of the adenosine A 2A receptor associated with the induction of diabetes in SHR when compared with normoglycemic SHR [ 29 ]. Furthermore, we previously reported that CADO treatment improved glucose metabolism (decreased hyperglycemia and glycosuria) and renal function (decreased proteinuria) [ 20 ].…”
Section: Discussionmentioning
confidence: 77%
“…As such, treatment with CADO is also associated with decreased renal fibrosis, which can be a result of increased anti-fibrotic adenosine A 2A receptors [ 4 , 48 ]. Taken together, these studies of our group, performed in the same experimental conditions, show that in SHR, induction of diabetes with STZ decreases the expression of renal adenosine A 2A receptors [ 29 ] and that exogenously stimulating adenosine receptors can partially restore that lessened expression of the adenosine A 2A receptor. This positive modulatory role of exogenous adenosine (here mimicked by CADO infusion) seems to be specific for the adenosine A 2A receptor since we observed no alteration in the expression of A 1 , A 2B , or A 3 receptors in these renal structures.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations